Improve Gross Motor Skills Through Throw And Catch Ball Game In 3rd Grade School Students - Aditria, Intan Ayu Putri; Wismanadi, Himawan; Maharani, Virdia Devi (PHEDHERAL, 2023)
Gross motor skills involve body movements that engage all muscles and body parts or the overall body size affected by a child's level of maturity. The purpose of this research is to determine the influence of throw and catch ball game on the improvement of gross motor skills in students of Perak Barat IV/04 Surabaya Elementary School. This study is a qualitative descriptive research using action research methodology. The objective of this research is to enhance gross motor skills. The research design is based on the research model by Kemmis & Mc. Taggart. Data for this study were collected through observation sheets and documentation. Based on the results of Cycle 1, 15% of the children showed significant development, 20% developed as expected, 10% showed initial progress, and 45% did not show any progress. In Cycle 2, 20% of the children showed significant development, 40% developed as expected, 20% showed initial progress, and 20% did not show any progress. Therefore, it can be concluded that the results of this research prove that the throw and catch ball game can enhance children's gross motor skills.